STATUS SOSIAL EKONOMI PETERNAK KAMBING PERANAKAN ETAWA (PE) DI DESA SUNGAI LANGKA, KECAMATAN GEDONG TATAAN, KABUPATEN PESAWARAN PROVINSI LAMPUNG - Tri Rumiyani; Muhammad Dima Iqbal Hamdani (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
The aim of this research was to know social economic status of farmer groups Ettawa crossbred goat during the production and cost value of the milk. The research was held  on July – August 2016 in Ettawa farmer groups in Sungai Langka Village, Gedong Tataan District, Pesawaran Regency, Lampung Province. Material of this research were 40 samples from three farmer groups : Tunas Muda, Sehati jaya  and Margarini 6. The method of this research was a survey with purposive random sampling. Data were analyzed by descriptive analysis. The result showed each farmer groups had different social economic status during production and cost value of the milk. Keywords : Ettawa Crossbred Goat , Social Economic Status, Sungai Langka Village.